American Indian Apache Read and Color - Bischoff, Kay; Bischoff, Eugene H. (Albuquerque, NM Eukabi Publishers)
This leaflet is set up as a coloring book with different stories about the Apache Indians and their way of life.
g
Master list item #: 72
File location is in the New Mexico file Cabinet
Keywords: Apache Indians; Indian life and customs; Indian myth and legend; Indian History; Coloring Books